Our century - Pelešjan, Artavazd A.; Matt, Gerald; Stief, Angela (Kerber, 2004)
In the beginning was the film. On the work of the Armenian film director and film thinker, Artavazd Peleshian Constantin Wulff -- Paul Virilio -- The Inhabitants (1970) -- Distance montage, or the theory of distance Artavazd Peleschjan -- The Seasons (1972-75) -- Excerpt from the literarcy script Our century Artavazd Peleschjan -- Our century (1982/90) -- The literary script Mirage Artavazd Peleschjan -- A language before Babel. Film conversation between Artavazd Peleshian and Jean-Luc Godard -- Artavazd Pelshian, or, Reality taken apart François Niney